The prevalence and risk factors of intraoperative hypothermia in patients with hip/knee arthroplasty: a systematic review and meta-analysis - Bingxin Fan; Boliang Li; Zhi Wang; Hao Wu; Li Huang; Surong Liu (BMC Musculoskeletal Disorders)
Abstract Background Intraoperative hypothermia (IOH) is common among patients undergoing total joint arthroplasty (TJA) of the lower extremities. Evaluating the risk factors for IOH is critical for the success of preventive interventions. This study aims to systematically assess the prevalence and risk factors of IOH in TJA patients. Design Systematic review and meta-analysis. Methods Two independent researchers conducted a literature search across eight databases: PubMed, Web of Science, Embase, Cochrane Library, CNKI, VIP, WANFANG Data, and CBM. The quality of included studies was assessed using the Newcastle-Ottawa Scale. A random-effects model was employed to analyze the prevalence and risk factors of IOH. All analyses were performed using Stata 12.0 software. Results Across 21 cohort studies on TJA patients, the pooled prevalence of IOH was 35.28% (95% CI: 27.50%-43.48%). Subgroup analysis revealed an IOH prevalence of 38.66% (95% CI: 28.67%-49.16%) in THA patients and 27.23% (95% CI: 18.37%- 37.11%) in TKA patients. Significant risk factors for IOH included intraoperative blood loss, intraoperative infusion volume, operating room temperature, and surgical time. Current evidence does not support a clear association between patient age, anesthesia time, and IOH. Conclusion Our Meta-analysis indicates that the prevalence of IOH is high among TJA patients, despite significant heterogeneity (I² =98.7%, τ²= 0.15), the pooled analysis suggested the prevalence of IOH in TJA patients was 35.28% (95% CI: 27.50%-43.48%). However, the interpretation of these findings should be cautious due to substantial variability across studies. Additionally, assessment of intraoperative blood loss, infusion volume, operating room temperature, and surgical time should be integral to IOH risk evaluation in TJA patients. Future studies are needed to further explore the roles of age and anesthesia time as potential risk factors. Tailored IOH prevention strategies should be developed by addressing modifiable risk factors. Trial registration PROSPERO Registration ID: CRD42024559846